Mitochondria and apoptosis - Tait, Stephen (Henry Stewart Talks, 2021)
Apoptosis, Caspase activation and function in apoptosis, Mitochondrial/intrinsic pathway of apoptosis, Mitochondrial outer membrane permeabilisation (MOMP), BCL-2 family proteins role in mitochondrial permeabilisation, Targeting mitochondrial apoptosis in disease, Caspase-independent cell death